Evaluating Stunting Prevention Policy Advocacy at the Sub-District Level in Indonesia - Indah, Sentia; Asnil, Asnil (Journal of Governance and Public Policy, 2026)
Stunting remains a major public health problem in Indonesia due to its impact on physical growth, cognitive development, long-term health, and economic productivity. Although the government has issued several regulations, including Presidential Regulation No. 72 of 2021 on the Acceleration of Stunting Reduction, the effectiveness of their implementation at the local level, particularly in policy advocacy, has rarely been examined in depth. In Pancung Soal Subdistrict, stunting prevalence increased from 27 cases in 2022 to 44 cases in 2024, reflecting limited program outcomes. This study aims to evaluate the effectiveness of stunting prevention policy advocacy implementation using a qualitative descriptive approach through in-depth interviews and document analysis. The analysis focuses on four main advocacy strategies: stunting deliberation forums (rembuk stunting), audience meetings, workshops, and media campaigns. The findings revealed that advocacy efforts remain ineffective due to limitations in human resources, budget allocation, infrastructure, and public awareness. Advocacy activities have not been conducted comprehensively or systematically and lack structured evaluation mechanisms. From a theoretical perspective, this study contributes to the international literature by providing insights from the sub-district level, a context rarely explored in global discourse. It emphasizes the importance of integrating community-based advocacy into the public policy cycle, ensuring that advocacy is linked to policy formulation, implementation, and evaluation. The findings underscore the need for multi-sectoral governance, institutional coordination, digital media integration, and continuous monitoring systems. This study offers a new perspective on local (indigenous) advocacy in resource-constrained settings and serves as a foundation for future comparative and mixed-methods research.